PENGARUH KARAKTERISTIK INDIVIDU DAN MOTIVASI INTRINSIK TERHADAP KOMITMEN AFEKTIF DAN KINERJA PEGAWAI - Linda Emiyanti; Eny Rochaida; Irsan Tricahyadinata (The Manager Review, 2020)
Employee’s performance is the most important key to achieve organizational purpose.  The hospital is engaged in the health sector by conducting management based on management of business entities. Hospital needs to give attention to its human resources in order to improve hospital services. The purpose of this study is to examine and analyze the influence of individual characteristics on employee's affective commitment. Test and analyze the effect of Intrinsic Motivation on Employee Affective Commitments. Test and analyze the influence of individual characteristics on employee performance. Test and analyze the effect of Intrinsic Motivation on Employee Performance. Test and analyze the effect of Affective Commitment on Employee Performance. In order to test the hypothesis analyze the author uses the Structural Equation Modeling analysis tool with SmartPLS. Respondents of this study were Administration Employees RSUD A. Wahab Sjahranie Samarinda with a total sample of 60 respondents. Data collection technique are library research, questioners and interviews. The results of the analysis show that individual characteristics have positive and significant effect on affective commitment. Intrinsic Motivation has positive and significant effect on affective commitment. Individual characteristics have positive and unsignificant effect on employee performance. Intrinsic Motivation has unsignificant negative effect on employee performance and affective commitment has  significant on employee performance.